A Bibliometric Analysis of Moodle E-learning: Evidence from 2011 to 2021 - Hijril Ismail (Universitas Jambi, Indonesia, 2022)
Moodle e-learning is a suitable solution for learning in the technology era. The research purpose was to present a comprehensive literature review on Moodle e-learning in teaching and learning. The Articles were gained via Publish or Perish Software. The study analyzed 29 articles from 2011 to 2021 from the Scopus database. The Software of Mendeley was utilized to arrange the articles. The Software of Vosviewer is applied to review and identify the articles. The study showed the two clusters of group words that appear most often. The first cluster consisted of six items (application, e-learning, effective, elementary school, Moodle, and study) and the second cluster consisted of three items words (design, development, and Moodle). This cluster represents the research streams of Moodle e-learning.